Report on assessment of selected One Health resources for eastern and southern Africa - Kang’ethe, Erastus K.; Kiugu, E.; Muriuki, S.; Richards, Shauna; Quan, M.; Mutua, Florence; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2024)
The One Health approach is an integrated, unifying approach that aims to sustainably optimize the health of people, animals, and ecosystems, and recognizes the health of humans, domestic and wild animals, plants, and the wider environment are linked and interdependent1. It mobilizes multiple sectors, disciplines, and stakeholders to foster wellbeing and tackle threats to health and ecosystems. The Joint Plan of Action (JPA) developed by the One Health High-Level Expert Panel (OHHLEP) aims to enhance One Health (OH) capacities to strengthen health systems among other objectives. The Capacitating One Health in Eastern and Southern Africa (COHESA) project was interested in knowing each resource's strength in areas of One Health and capacity building in Eastern and Southern Africa. To achieve this the project developed a rubric based on 20 descriptive and 7 weighted indicators to assess the selected resources. A team of consultants further developed the rubric, pretested it, and finally used it to evaluate 36 resources. This process necessitated working closely with the team member who developed the rubric structure and the work package three teams at the International Livestock Research Institute (ILRI). Thirty-six resources mainly from the Africa One Health University Network (AFROHUN) (41.7%) and the One Health Regional Network for the Horn of Africa (HORN) (22.2 %) consortia were assessed, most of which were training manuals (86%). Most of the resources targeted professionals, researchers, and graduate students (92%). They were delivered as short courses that lasted for 1-12 hours (33.3%), 1-6 days (30.6 %), and over 2 years (5.6%.).